Classification, grading criteria and quantitative expression of earth fissures: a case study in Daming Area, North China Plain. Issue 1 (1st January 2018) - Xu, Jishan; Peng, Jianbing; Deng, Yahong; He, Hongqian; Meng, Lingchao; Wang, Feiyong
Abstract: Observation, description and preliminary analysis are important means in studies on earth fissures. As a phenomenon of surface fractures, earth fissures are formed under the joint action of exogenetic and endogenetic forces and their development can be characterized by parameters of length, width, depth, fractal dimension and influential width. Based on their length, we deduced a 'length-grade conversion equation' and divided earth fissures into 10 grades. In addition, we also deduced a series functions to describe the contribution of fissure-inducing forces including active fault, earthquake, groundwater withdrawal and ancient river channels based on their roles in fissure formation and their affecting conditions. These functions provide the criteria for classification of earth fissures. In order to verify the effectiveness of these methods, we took Daming fracture zone on the North China Plain as an example to quantitatively calculate the control factors of the earth fissures in this area. Moreover, we proposed various plane expression methods for single and grouped earth fissures that could be used to improve the relevant studies on earth fissures.